(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article examines the importance of stylistic analysis of two outstanding works in the global context of literary heritage: Judith McNaught’s novel "Almost Heaven" and Abdullah Qodiriy’s novel "O’tkan kunlar" ("Days Gone By"). The uniqueness of this analysis lies in the comparison of literary works originating from diverse cultural and historical traditions, which is a key aspect in contemporary literary discourse.